A newly identified secreted larval antigen elicits basophil-dependent protective immunity against N. brasiliensis infection - Thuma, Natalie; Döhler, Daniela; Mielenz, Dirk; Sticht, Heinrich; Radtke, Daniel; Reimann, Lena; Warscheid, Bettina; Voehringer, David (Frontiers in Immunology, 2022)
Hookworms infect more that 400 million people and cause significant socio-economic burden on endemic countries. The lack of efficient vaccines and the emergence of anthelminthic drug resistance are of major concern. Free-living hookworm larvae infect their hosts via the skin and live as adult worms in the small intestine where they feed on host tissue and blood. Excretory/secretory (E/S) products, released by helminths as they migrate through their host, are thought to play a key role in facilitating infection and successful establishment of parasitism. However, E/S products can also elicit protective immune responses that might be harnessed for vaccine development. By performing Western blots with serum of Nippostrongylus brasiliensis (Nb) infected mice as a model for human hookworm infection, we identified a largely overlapping set of IgG1- and IgE-reactive antigens in E/S from infective L3 stage larvae. Mass spectrometry analysis led to the identification of a new protein family with 6 paralogues in the Nb genome which we termed Nb-LSA1 for “Nippostrongylus brasiliensis larval secreted protein 1”. The recombinantly expressed 17 kDa family member Nb-LSA1a was recognized by antibodies in the serum of Nb immune mice. Immunization of mice with Nb-LSA1a in alum elicited a strong IgG1 response but no detectable antigen-specific IgE. Most importantly, immunized mice were largely protected against a challenge Nb infection. This effect was dependent on the presence of basophils and occurred before the parasites reached the intestine. Therefore, basophils appear to play a critical role for rapid control of infection with L3 stage larvae in mice immunized with a single secreted larval protein. A better understanding of basophil-mediated protective immunity and identification of potent larval antigens of human hookworms could help to develop promising vaccination strategies.